Fecundity in sterility - Cesari, Giuseppe (Medicina e Morale, 1993)
Fecundity and fertility are not synonymous: the former belongs to an exclusive dimension of "human nature"; the latter only concerns the biological dimension of fecundity. Starting with this statement, the Author underlines how human nature, that is not limited to the organic and mental dimensions, is completely realized in the noethical dimension (logos). In fact man is the only living being that questions himself on the meaning and the consequences of his actions. lt's in the third dimension that one can find the interpretations of human behaviour and desires, like for example, the desire to have a child. But having a child not necessarily depends on just having it: being a mother and a father is a noethical reality even before and more than it's a biological (somatopsychic) fact.